Synthesis and application of trifluoroethoxy-substituted phthalocyanines and subphthalocyanines - Mori, Satoru; Shibata, Norio (Beilstein Journal of Organic Chemistry, 2017)
Phthalocyanines and subphthalocyanines are attracting attention as functional dyes that are applicable to organic solar cells, photodynamic therapy, organic electronic devices, and other applications. However, phthalocyanines are generally difficult to handle due to their strong ability to aggregate, so this property must be controlled for further applications of phthalocyanines. On the other hand, trifluoroethoxy-substituted phthalocyanines are known to suppress aggregation due to repulsion of the trifluoroethoxy group. Furthermore, the electronic characteristics of phthalocyanines are significantly changed by the strong electronegativity of fluorine. Therefore, it is expected that trifluoroethoxy-substituted phthalocyanines can be applied to new industrial fields. This review summarizes the synthesis and application of trifluoroethoxy-substituted phthalocyanine and subphthalocyanine derivatives.
Keywords: aggregation; fluorine; phthalocyanine; subphthalocyanine; trifluoroethoxy

Phthalocyanines, Properties and Applications - Lever, A. B. P.; Milaeva, E. R.; Speier, G. (VCH, 1993)

Handbook of Advanced Electronic and Photonic Materials - de la Torre, G.; Nicolau, M.; Torres, T. (Wiley, 2001)

The Porphyrin Handbook - Erk, P.; Hengelsberg, H. (Applications of Phthalocyanines, 2003)

(untitled) - Dent, C. E.; Linstead, R. P. (J. Chem. Soc., 1934)

(untitled) - Tianyong, Z.; Chunlong, Z. (Dyes Pigm., 1997)

(untitled) - Lelu, S.; Novat, C.; Graillat, C.; Guyot, A.; Bourgeat-Lami, E. (Polym. Int., 2003)

(untitled) - Defeyt, C.; Vandenabeele, P.; Gilbert, B.; Van Pevenage, J.; Cloots, R.; Strivay, D. (J. Raman Spectrosc., 2012)

(untitled) - Gregory, P. (J. Porphyrins Phthalocyanines, 2000)

Proceedings of the Second International Symposium on Chemistry of Functional Dyes - Yoshida, Z.; Shirota, Y. (Chemistry of Functional Dyes, 1993)

Molecular Design of Functional Dyes-PPP Molecular Orbital Method and Its Applications - Tokita, S.; Matsuoka, M.; Kogo, Y.; Kihara, H. (Maruzen, 1989)

Functional Dyes - Kim, S.-H. (Elsevier, 2006)

(untitled) - Choi, J.; Kim, S. H.; Lee, W.; Yoon, C.; Kim, J. P. (New J. Chem., 2012)

(untitled) - Kim, Y. D.; Kim, J. P.; Kwon, O. S.; Cho, I. H. (Dyes Pigm., 2009)

(untitled) - Rollet, F.; Morlat-Thérias, S.; Gardette, J.-L.; Fontaine, J.-M.; Perdereau, J.; Polack, J.-D. (J. Cultural Heritage, 2008)

(untitled) - Cid, J.-J.; García-Iglesias, M.; Yum, J.-H.; Forneli, A.; Albero, J.; Martínez-Ferrero, E.; Vázquez, P.; Grätzel, M.; Nazeeruddin, M. K.; Palomares, E.; Torres, T. (Chem. – Eur. J., 2009)

(untitled) - O'Regan, B. C.; López-Duarte, I.; Martínez-Díaz, M. V.; Forneli, A.; Albero, J.; Morandeira, A.; Palomares, E.; Torres, T.; Durrant, J. R. (J. Am. Chem. Soc., 2008)

(untitled) - Bonnett, R. (Chem. Soc. Rev., 1995)

(untitled) - Berger, R.; Resnati, G.; Metrangolo, P.; Weber, E.; Hulliger, J. (Chem. Soc. Rev., 2011)

Electronegativity - Sen, K. D.; Jørgensen, C. K. (Springer, 1987)

(untitled) - Nagle, J. K. (J. Am. Chem. Soc., 1990)

(untitled) - O’Hagan, D.; Rzepa, H. S. (Chem. Commun., 1997)

(untitled) - Park, B. K.; Kitteringham, N. R. (Drug Metab. Rev., 1994)

(untitled) - O’Hagan, D. (Chem. Soc. Rev., 2008)

Well Architectured Fluoropolymers: Synthesis, Properties and Applications - Ameduri, B.; Boutevin, B. (Elsevier, 2004)

(untitled) - Ismail, F. M. D. (J. Fluorine Chem., 2002)

(untitled) - Purser, S.; Moore, P. R.; Swallow, S.; Gouverneur, V. (Chem. Soc. Rev., 2008)

(untitled) - Isanbor, C.; O’Hagan, D. (J. Fluorine Chem., 2006)

(untitled) - Bégué, J.-P.; Bonnet-Delpon, D. (J. Fluorine Chem., 2006)

(untitled) - Kirk, K. L. (J. Fluorine Chem., 2006)

(untitled) - Hagmann, W. K. (J. Med. Chem., 2008)

Fluorine in Medicinal Chemistry and Chemical Biology - Ojima, I. (Wiley-Blackwell, 2009)

Fluorine in Heterocyclic Chemistry - Stuzhin, P. A. (Fluorinated Phthalocyanines and Their Analogues, 2014)

(untitled) - Boyle, R. W.; Rousseau, J.; Kudrevich, S. V.; Obochi, M. O. K.; van Lier, J. E. (Br. J. Cancer, 1996)

(untitled) - Ünlü, S.; Yaraşır, M. N.; Kandaz, M.; Koca, A.; Salih, B. (Polyhedron, 2008)

(untitled) - Selçukoğlu, M.; Hamuryudan, E. (Dyes Pigm., 2007)

(untitled) - Moons, H.; Loas, A.; Gorun, S. M.; Doorslaer, S. V. (Dalton Trans., 2014)

(untitled) - Bao, Z.; Lovinger, A. J.; Brown, J. (J. Am. Chem. Soc., 1998)

(untitled) - Yoon, S. M.; Song, H. J.; Hwang, I.-C.; Kim, K. S.; Choi, H. C. (Chem. Commun., 2010)

(untitled) - Meiss, J.; Merten, A.; Hein, M.; Schuenemann, C.; Schäfer, S.; Tietze, M.; Uhrich, C.; Pfeiffer, M.; Leo, K.; Riede, M. (Adv. Funct. Mater., 2012)

(untitled) - Cnops, K.; Zango, G.; Genoe, J.; Heremans, P.; Martinez-Diaz, M. V.; Torres, T.; Cheyns, D. (J. Am. Chem. Soc., 2015)

(untitled) - Mori, S.; Shibata, N. (J. Synth. Org. Chem., Jpn., 2016)

Proceedings of the 2nd International Symposium on the Chemistry of Functional Dye - Kobayashi, H.; Matsumoto, K.; Sonoda, T. (Kobe, 1992)

(untitled) - Kobayashi, N.; Sasaki, N.; Higashi, Y.; Osa, T. (Inorg. Chem., 1995)

(untitled) - Weitman, H.; Schatz, S.; Gottlieb, H. E.; Kobayashi, N.; Ehrenberg, B. (Photochem. Photobiol., 2001)

(untitled) - Hiroaki, I.; Yutaka, K.; Akiyuki, M. (Chem. Lett., 2004)

(untitled) - Reichardt, C. (Chem. Rev., 1994)

(untitled) - Kobayashi, N.; Ogata, H.; Nonaka, N.; Luk’yanets, E. A. (Chem. – Eur. J., 2003)

(untitled) - Liu, J.-B.; Zhao, Y.; Zhao, F.-Q.; Zhang, F.-S.; Tang, Y.-W.; Song, X.-q.; Zhou, F.-T. (Acta Phys.-Chim. Sin., 1996)

(untitled) - Beeby, A.; FitzGerald, S.; Stanley, C. F. (J. Chem. Soc., Perkin Trans. 2, 2001)

(untitled) - Honda, T.; Kojima, T.; Kobayashi, N.; Fukuzumi, S. (Angew. Chem., Int. Ed., 2011)

(untitled) - Leclaire, J.; Dagiral, R.; Fery-Forgues, S.; Coppel, Y.; Donnadieu, B.; Caminade, A.-M.; Majoral, J.-P. (J. Am. Chem. Soc., 2005)

(untitled) - Eberhardt, W.; Hanack, M. (Synthesis, 1997)

(untitled) - Nemykin, V. N.; Chernii, V. Ya.; Volkov, S. V.; Bundina, N. I.; Kaliya, O. L.; Li, V. D.; Lukyanets, E. A. (J. Porphyrins Phthalocyanines, 1999)

(untitled) - Iida, N.; Tanaka, K.; Tokunaga, E.; Mori, S.; Saito, N.; Shibata, N. (ChemistryOpen, 2015)

(untitled) - Das, B.; Tokunaga, E.; Shibata, N.; Kobayashi, N. (J. Fluorine Chem., 2010)

(untitled) - Jessop, P. G.; Ikariya, T.; Noyori, R. (Chem. Rev., 1999)

(untitled) - Cooper, A. I. (J. Mater. Chem., 2000)

(untitled) - Oakes, R. S.; Clifford, A. A.; Rayner, C. M. (J. Chem. Soc., Perkin Trans. 1, 2001)

(untitled) - Hay, J. N.; Khan, A. (J. Mater. Sci., 2002)

(untitled) - Hoggan, E. N.; Flowers, D.; Wang, K.; DeSimone, J. M.; Carbonell, R. G. (Ind. Eng. Chem. Res., 2004)

(untitled) - Xu, X.-H.; Kusuda, A.; Tokunaga, E.; Shibata, N. (Green Chem., 2011)

(untitled) - Xu, X.-H.; Azuma, A.; Taniguchi, M.; Tokunaga, E.; Shibata, N. (RSC Adv., 2013)

(untitled) - Kusuda, A.; Xu, X.-H.; Wang, X.; Tokunaga, E.; Shibata, N. (Green Chem., 2011)

(untitled) - Kobayashi, N.; Kondo, R.; Nakajima, S.; Osa, T. (J. Am. Chem. Soc., 1990)

(untitled) - Wang, A.; Long, L.; Zhang, C. (Tetrahedron, 2012)

(untitled) - Tian, M.; Wada, T.; Kimura-Suda, H.; Sasabe, H. (J. Mater. Chem., 1997)

(untitled) - Tian, M.; Wada, T.; Sasabe, H. (J. Heterocycl. Chem., 2000)

(untitled) - de la Torre, G.; Bottari, G.; Sekita, M.; Hausmann, A.; Guldi, D. M.; Torres, T. (Chem. Soc. Rev., 2013)

(untitled) - Maya, E. M.; Vázquez, P.; Torres, T. (Chem. – Eur. J., 1999)

(untitled) - Ali, H.; Baillargeon, P.; van Lier, J. E. (Tetrahedron Lett., 2008)

(untitled) - Ali, H.; van Lier, J. E. (Tetrahedron Lett., 2009)

(untitled) - Dodsworth, E. S.; Lever, A. B. P.; Seymour, P.; Leznoff, C. C. (J. Phys. Chem., 1985)

(untitled) - Tian, M.; Zhang, Y.; Wada, T.; Sasabe, H. (Dyes Pigm., 2003)

(untitled) - Yoshiyama, H.; Shibata, N.; Sato, T.; Nakamura, S.; Toru, T. (Chem. Commun., 2008)

(untitled) - Vigh, S.; Lam, H.; Janda, P.; Lever, A. B. P.; Leznoff, C. C.; Cerny, R. L. (Can. J. Chem., 1991)

(untitled) - García-Frutos, E. M.; O’Flaherty, S. M.; Maya, E. M.; de la Torre, G.; Blau, W.; Vázquez, P.; Torres, T. (J. Mater. Chem., 2003)

(untitled) - Kobayashi, N.; Lever, A. B. P. (J. Am. Chem. Soc., 1987)

(untitled) - Huang, X.; Zhao, F.; Li, Z.; Huang, L.; Tang, Y.; Zhang, F.; Tung, C.-H. (Chem. Lett., 2007)

(untitled) - Leznoff, C. C.; Marcuccio, S. M.; Greenberg, S.; Lever, A. B. P.; Tomer, K. B. (Can. J. Chem., 1985)

(untitled) - Leznoff, C. C.; Svirskaya, P. I.; Khouw, B.; Cerny, R. L.; Seymour, P.; Lever, A. B. P. (J. Org. Chem., 1991)

(untitled) - Yoshiyama, H.; Shibata, N.; Sato, T.; Nakamura, S.; Toru, T. (Org. Biomol. Chem., 2008)

(untitled) - Yoshiyama, H.; Shibata, N.; Sato, T.; Nakamura, S.; Toru, T. (Org. Biomol. Chem., 2009)

(untitled) - Durmaz, H.; Sanyal, A.; Hizal, G.; Tunca, U. (Polym. Chem., 2012)

(untitled) - Das, B.; Umeda, M.; Tokunaga, E.; Toru, T.; Shibata, N. (Chem. Lett., 2010)

(untitled) - Allémann, E.; Rousseau, J.; Brasseur, N.; Kudrevich, S. V.; Lewis, K.; van Lier, J. E. (Int. J. Cancer, 1996)

(untitled) - Liu, K. J.; Gast, P.; Moussavi, M.; Norby, S. W.; Vahidi, N.; Walczak, T.; Wu, M.; Swartz, H. M. (Proc. Natl. Acad. Sci. U. S. A., 1993)

(untitled) - Mantareva, V.; Kussovski, V.; Angelov, I.; Wöhrle, D.; Dimitrov, R.; Popova, E.; Dimitrov, S. (Photochem. Photobiol. Sci., 2011)

(untitled) - De Filippis, M. P.; Dei, D.; Fantetti, L.; Roncucci, G. (Tetrahedron Lett., 2000)

(untitled) - Li, H.; Jensen, T. J.; Fronczek, F. R.; Vicente, M. G. H. (J. Med. Chem., 2008)

(untitled) - Ribeiro, A. O.; Tomé, J. P. C.; Neves, M. G. P. M. S.; Tomé, A. C.; Cavaleiro, J. A. S.; Iamamoto, Y.; Torres, T. (Tetrahedron Lett., 2006)

(untitled) - Zorlu, Y.; Dumoulin, F.; Bouchu, D.; Ahsen, V.; Lafont, D. (Tetrahedron Lett., 2010)

(untitled) - Sibrian-Vazquez, M.; Ortiz, J.; Nesterova, I. V.; Fernández-Lázaro, F.; Sastre-Santos, A.; Soper, S. A.; Vicente, M. G. H. (Bioconjugate Chem., 2007)

(untitled) - Ali, H.; Ait-Mohand, S.; Gosselin, S.; van Lier, J. E.; Guérin, B. (J. Org. Chem., 2011)

(untitled) - Nyman, E. S.; Hynninen, P. H. (J. Photochem. Photobiol., B: Biol., 2004)

(untitled) - Kuimova, M. K.; Botchway, S. W.; Parker, A. W.; Balaz, M.; Collins, H. A.; Anderson, H. L.; Suhling, K.; Ogilby, P. R. (Nat. Chem., 2009)

(untitled) - Macdonald, I. J.; Dougherty, T. J. (J. Porphyrins Phthalocyanines, 2001)

Cancer Nanotechnology Methods and Protocols - Greish, K. (Enhanced Permeability and Retention (EPR) Effect for Anticancer Nanomedicine Drug Targeting, 2010)

(untitled) - Erbas, S.; Gorgulu, A.; Kocakusakogullari, M.; Akkaya, E. U. (Chem. Commun., 2009)

(untitled) - Reddy, M. R.; Shibata, N.; Kondo, Y.; Nakamura, S.; Toru, T. (Angew. Chem., Int. Ed., 2006)

(untitled) - Obata, T.; Mori, S.; Suzuki, Y.; Kashiwagi, T.; Tokunaga, E.; Shibata, N.; Tanaka, M. (J. Cancer Ther., 2015)

(untitled) - D'Souza, F.; Ito, O. (Coord. Chem. Rev., 2005)

(untitled) - Mishra, A.; Bäuerle, P. (Angew. Chem., Int. Ed., 2012)

(untitled) - Linssen, T. G.; Dürr, K.; Hanack, M.; Hirsch, A. (J. Chem. Soc., Chem. Commun., 1995)

(untitled) - Sukeguchi, D.; Yoshiyama, H.; Singh, S. P.; Shibata, N.; Nakamura, S.; Toru, T.; Hayashi, Y.; Soga, T. (Heterocycl. Commun., 2009)

(untitled) - Sukeguchi, D.; Yoshiyama, H.; Shibata, N.; Nakamura, S.; Toru, T.; Hayashi, Y.; Soga, T. (J. Fluorine Chem., 2009)

(untitled) - Guo, J.; Liang, Y.; Szarko, J.; Lee, B.; Son, H. J.; Rolczynski, B. S.; Yu, L.; Chen, L. X. (J. Phys. Chem. B, 2010)

(untitled) - Dang, M. T.; Hirsch, L.; Wantz, G. (Adv. Mater., 2011)

(untitled) - Yamada, I.; Umeda, M.; Hayashi, Y.; Soga, T.; Shibata, N. (Jpn. J. Appl. Phys., 2012)

(untitled) - Yamada, I.; Iida, N.; Hayashi, Y.; Soga, T.; Shibata, N. (Jpn. J. Appl. Phys., 2013)

(untitled) - Rand, B. P.; Cheyns, D.; Vasseur, K.; Giebink, N. C.; Mothy, S.; Yi, Y.; Coropceanu, V.; Beljonne, D.; Cornil, J.; Brédas, J.-L.; Genoe, J. (Adv. Funct. Mater., 2012)

Fluoropolymers: Synthesis and Applications - Hougham, G.; Cassidy, P. E.; Johns, K.; Davidson, T. (Plenum Publishers, 1999)

(untitled) - Gritsenko, K. P.; Dimitriev, O. P.; Kislyk, V. V.; Getsko, O. M.; Schrader, S.; Brehmer, L. (Colloids Surf., A, 2002)

(untitled) - Wang, J.-W.; Shen, Q.-D.; Bao, H.-M.; Yang, C.-Z.; Zhang, Q. M. (Macromolecules, 2005)

(untitled) - Tillet, G.; De Leonardis, P.; Alaaeddine, A.; Umeda, M.; Mori, S.; Shibata, N.; Aly, S. M.; Fortin, D.; Harvey, P. D.; Ameduri, B. (Macromol. Chem. Phys., 2012)

(untitled) - Kondratenko, N. V.; Nemykin, V. N.; Lukyanets, E. A.; Kostromina, N. A.; Volkovan, S. V.; Yagupolskii, L. M. (J. Porphyrins Phthalocyanines, 1997)

(untitled) - Winter, G.; Heckmann, H.; Haisch, P.; Eberhardt, W.; Hanack, M.; Lüer, L.; Egelhaaf, H.-J.; Oelkrug, D. (J. Am. Chem. Soc., 1998)

(untitled) - Gao, L.; Qian, X. (J. Fluorine Chem., 2002)

(untitled) - Sukeguchi, D.; Yoshiyama, H.; Shibata, N.; Nakamura, S.; Toru, T. (Heterocycl. Commun., 2009)

(untitled) - Mori, S.; Ogawa, N.; Tokunaga, E.; Shibata, N. (J. Porphyrins Phthalocyanines, 2014)

(untitled) - Ishikawa, N.; Sugita, M.; Ishikawa, T.; Koshihara, S.; Kaizu, Y. (J. Am. Chem. Soc., 2003)

(untitled) - Ye, T.; Takami, T.; Wang, R.; Jiang, J.; Weiss, P. S. (J. Am. Chem. Soc., 2006)

(untitled) - Kobayashi, N. (J. Porphyrins Phthalocyanines, 1999)

(untitled) - Claessens, C. G.; González-Rodríguez, D.; Torres, T. (Chem. Rev., 2002)

(untitled) - Torres, T. (Angew. Chem., Int. Ed., 2006)

(untitled) - Shimizu, S.; Kobayashi, N. (Chem. Commun., 2014)

(untitled) - Sastre, A.; Torres, T.; Díaz-García, M. A.; Agulló-López, F.; Dhenaut, C.; Brasselet, S.; Ledoux, I.; Zyss, J. (J. Am. Chem. Soc., 1996)

(untitled) - González-Rodríguez, D.; Torres, T.; Guldi, D. M.; Rivera, J.; Echegoyen, L. (Org. Lett., 2002)

(untitled) - Mutolo, K. L.; Mayo, E. I.; Rand, B. P.; Forrest, S. R.; Thompson, M. E. (J. Am. Chem. Soc., 2006)

(untitled) - Shibata, N.; Das, B.; Tokunaga, E.; Shiro, M.; Kobayashi, N. (Chem. – Eur. J., 2010)

(untitled) - Claessens, C. G.; Gonzalez-Rodríguez, D.; Rodríguez-Morgade, M. S.; Medina, A.; Torres, T. (Chem. Rev., 2014)

(untitled) - Mori, S.; Ogawa, N.; Tokunaga, E.; Shibata, N. (Dalton Trans., 2015)

(untitled) - Guilleme, J.; González-Rodríguez, D.; Torres, T. (Angew. Chem., Int. Ed., 2011)

(untitled) - Kossanyi, J.; Chahraoui, D. (Int. J. Photoenergy, 2000)

(untitled) - Mori, S.; Ogawa, N.; Tokunaga, E.; Tsuzuki, S.; Shibata, N. (Dalton Trans., 2016)

(untitled) - Leznoff, C. C.; Lam, H.; Marcuccio, S. M.; Nevin, W. A.; Janda, P.; Kobayashi, N.; Lever, A. B. P. (J. Chem. Soc., Chem. Commun., 1987)

(untitled) - Kobayashi, N. (J. Chem. Soc., Chem. Commun., 1991)

(untitled) - Claessens, C. G.; Torres, T. (Angew. Chem., Int. Ed., 2002)

(untitled) - Fukuda, T.; Stork, R. J.; Potucek, R. J.; Olmstead, M. M.; Noll, B. C.; Kobayashi, N.; Durfee, W. S. (Angew. Chem., Int. Ed., 2002)

(untitled) - Kobayashi, N.; Lam, H.; Nevin, W. A.; Janda, P.; Leznoff, C. C.; Koyama, T.; Monden, A.; Shirai, H. (J. Am. Chem. Soc., 1994)

(untitled) - Zango, G.; Zirzlmeier, J.; Claessens, C. G.; Clark, T.; Martínez-Díaz, M. V.; Guldi, D. M.; Torres, T. (Chem. Sci., 2015)

(untitled) - Shibata, N.; Mori, S.; Hayashi, M.; Umeda, M.; Tokunaga, E.; Shiro, M.; Sato, H.; Hoshi, T.; Kobayashi, N. (Chem. Commun., 2014)